An Analysis on Undergraduate Students’ Theses Background Writing in English Study Program at IAIN Bone - Aprianar, Elda; Jafar, Muhammad Basri; Amin, Fatimah Hidayahni (Journal of Excellence in English Language Education, 2023)
The goal of this study was specified to analyze the development of writing aspects of undergraduate students’ theses background in English Study Program at IAIN Bone. This research used descriptive qualitative method.  The sample of this research was 10 undergraduate students’ theses background. The undergraduate students’ compositions were analyzed and reviewed frequently using Jacob et al. (1981) rubric. The findings revealed that all undergraduate students developed their background in inductive way; they first stated the general premises of their idea and then form a specific conclusion at the end, they organized their sentences and paragraphs by using cohesive device. The researcher also found that undergraduate students had various writing problems such as lack in organizing their ideas, grammatical mistakes that were tense, agreement, word order, article, and preposition, mistake usage of vocabulary that were inappropriate words and word placement, and mechanical mistakes that were spelling, punctuation and capitalization. As a result, the researcher found that, in this degree, undergraduate students still encountered problems in writing their theses background. Thus, English lecturers at IAIN Bone could more aware and focus on their students’ writing compositions by looking, improving, and guiding their students on how to develop their content, organize their sentence and paragraph, use appropriate vocabulary, use correct language use and mechanic aspect.